1995
DOI: 10.1073/pnas.92.7.2760
|View full text |Cite
|
Sign up to set email alerts
|

Mutated K65R recombinant reverse transcriptase of human immunodeficiency virus type 1 shows diminished chain termination in the presence of 2',3'-dideoxycytidine 5'-triphosphate and other drugs.

Abstract: A lysine-to-arginine substitution at amino acid 65 (K65R) in human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT) is associated with resistance to 2',3'-dideoxycytidine (ddC), 2',3'-dideoxyinosine (ddI), and the (-) enantiomer of 2',3'-dideoxy-3'-thiacytidine (3TC). To further characterize the molecular basis of such resistance, we expressed the p66/pSi heterodimer of wildtype RT, K65R mutated RT, and a doubly mutated (K65R/M184V) RT in Escherichia coli and assessed the characteristics of nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
83
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 20 publications
(20 reference statements)
5
83
1
1
Order By: Relevance
“…This alteration in turn can lead to changes in fidelity. This hypothesis is supported by evidence from mutations introduced at positions K65 and Q151 of recombinant HIV-1 RT, which exhibited decreased mispair extension in vitro as well as resistance to a number of dideoxynucleoside analogs such as 2Ј,3Ј-dideoxy-3Ј-thiacytidine, 3Ј-azido-3Ј-deoxythymidine, 2Ј,3Ј-dideoxycytidsine, and 2Ј,3Ј-dideoxyinosine (14,18,47). Finally, a number of mutations introduced at residue Y115 of HIV-1 RT were shown to affect the frequency of misinsertions and mispair extensions (35,36).…”
supporting
confidence: 52%
“…This alteration in turn can lead to changes in fidelity. This hypothesis is supported by evidence from mutations introduced at positions K65 and Q151 of recombinant HIV-1 RT, which exhibited decreased mispair extension in vitro as well as resistance to a number of dideoxynucleoside analogs such as 2Ј,3Ј-dideoxy-3Ј-thiacytidine, 3Ј-azido-3Ј-deoxythymidine, 2Ј,3Ј-dideoxycytidsine, and 2Ј,3Ј-dideoxyinosine (14,18,47). Finally, a number of mutations introduced at residue Y115 of HIV-1 RT were shown to affect the frequency of misinsertions and mispair extensions (35,36).…”
supporting
confidence: 52%
“…This K65R mutation has been observed previously in vitro and confers resistance to 3TC, ddC (Gu et al, 1994), PMEA (Gu et al, 1995a;Taylor et al, 1996) and abacavir (Tisdale et al, 1997). The 65R/184V double mutant has also been previously observed in a patient on ddC therapy (Gu et al, 1995b). This virus with dual codon changes at positions 65 and 184 showed only low-level resistance to dOTC (<5-fold).…”
Section: Discussionmentioning
confidence: 80%
“…Crystallographic and modelling studies showed that the side chain of lysine at position 65 contacts the γ-phosphate of the incoming nucleotide and stacks over arginine at position 72 (Huang et al, 1999). In vitro, RT containing the K65R mutation displayed decreased affinity for the triphosphates of 3TC and ddC, resulting in diminished incorporation and chain termination (Arion et al, 1996;Gu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%